The structure of genetic and environmental risk factors for fears and phobias. Issue 11 (16th December 2013) - Loken, E. K.; Hettema, J. M.; Aggen, S. H.; Kendler, K. S.
Abstract : Background: Although prior genetic studies of interview-assessed fears and phobias have shown that genetic factors predispose individuals to fears and phobias, they have been restricted to the DSM-III to DSM-IV aggregated subtypes of phobias rather than to individual fearful and phobic stimuli. Method: We examined the lifetime history of fears and/or phobias in response to 21 individual phobic stimuli in 4067 personally interviewed twins from same-sex pairs from the Virginia Adult Twin Study of Psychiatric and Substance Abuse Disorders (VATSPSUD). We performed multivariate statistical analyses using Mx and Mplus. Results: The best-fitting model for the 21 phobic stimuli included four genetic factors (agora-social-acrophobia, animal phobia, blood-injection-illness phobia and claustrophobia) and three environmental factors (agora-social-hospital phobia, animal phobia, and situational phobia). Conclusions: This study provides the first view of the architecture of genetic and environmental risk factors for phobic disorders and their subtypes. The genetic factors of the phobias support the DSM-IV and DSM-5 constructs of animal and blood-injection-injury phobias but do not support the separation of agoraphobia from social phobia. The results also do not show a coherent genetic factor for the DSM-IV and DSM-5 situational phobia. Finally, the patterns of co-morbidity across individual fears and phobias produced by genetic and environmental influences differ appreciably.